2013
DOI: 10.19026/rjaset.6.3623
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Energy Efficiency in Heterogeneous Network

Abstract: Cellular networks are undergoing transformation from conventional homogeneous macro Base Stations (BSs) to Heterogeneous Network (HetNet). This new paradigm not only offers a significant improvement in the overall network capacity or user data rate; it also promises an improvement in the overall network Energy Efficiency (EE). In this study, a theoretical model for evaluating the EE in HetNet is developed. A HetNet generally consists of different types of Base Stations (BSs) which operate in harmony towards a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A green planning for energy-efficient wireless network design is presented in [43] [44] [45]. Optimizations of the BS size, location and density have been investigated in [13], [40], [41], [46]- [52], where the tradeoff between EE and deployment cost is also discussed. It is shown that an optimal number of BSs or cell size with minimal power consumption exists.…”
Section: Network Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…A green planning for energy-efficient wireless network design is presented in [43] [44] [45]. Optimizations of the BS size, location and density have been investigated in [13], [40], [41], [46]- [52], where the tradeoff between EE and deployment cost is also discussed. It is shown that an optimal number of BSs or cell size with minimal power consumption exists.…”
Section: Network Planningmentioning
confidence: 99%
“…BSs cell size optimization [13], [46], [47], [89], [90] BSs density optimization [19], [52], [70], [91] BSs location optimization [48], [57], [92], [93] Network operation and management…”
Section: Reviews On Energy-awareness In Heterogeneous Cellular Networkmentioning
confidence: 99%
“…A HetNet, as shown in Figure 1, is a multilayer network comprising of different types of base stations (macro, micro, pico, and femto) that have different transmission powers and coverage areas, with the sole aim of improving the overall network energy efficiency [4]. Picocells are mostly preferred in the HetNets, because of ease of planning and deployment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Energy Efficiency (EE) and Area Energy Efficiency (AEE) are other performance indicators that are improved with SBSs when deployed within macrocells [4]. In [5], it is observed that there exists an optimal number of SBSs per MBS that maximizes overall EE and AEE. Moreover, if percentage area of the MBS overlaid by SBSs increases, AEE is also increased.…”
Section: Introductionmentioning
confidence: 99%